2021
DOI: 10.1055/s-0041-1740464
|View full text |Cite
|
Sign up to set email alerts
|

Regional Gestational Age and Gender-Specific Birth Weight Reference Charts and its Comparison with Existing National and International Standards: A Cross-Sectional Study

Abstract: Background Growth potential is influenced by race, ethnicity, and environmental factors and assessment of growth using standardized charts is important for quality improvement initiatives in health care delivery and public health interventions of any nation. Objective This article aims to develop regional gestational age and gender-specific reference for birth weight and to compare it with published literature. Methodology This study was conducted in a teaching hospital in Puducherry, India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A study published by Tuzun et al [ 22 ] in 2017 involving 248 preterm neonates showed the incidence of LGA as 6% according to both Fenton 2013 and IG-21. A study by Prakash et al [ 23 ] from South India involving 2507 neonates observed discrepancies in the detection of LGA between Fenton 2013 (1.4%) and IG-21 (5.5%). These differences among the international charts that are generally used for labeling neonates as SGA and LGA are important and should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…A study published by Tuzun et al [ 22 ] in 2017 involving 248 preterm neonates showed the incidence of LGA as 6% according to both Fenton 2013 and IG-21. A study by Prakash et al [ 23 ] from South India involving 2507 neonates observed discrepancies in the detection of LGA between Fenton 2013 (1.4%) and IG-21 (5.5%). These differences among the international charts that are generally used for labeling neonates as SGA and LGA are important and should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%